CDK4/6 Inhibitor PD0332991 in Glioblastoma Treatment: Does It Have a Future? - Schröder, Lisette B. W.; McDonald, Kerrie L. (Frontiers in Oncology, 2015)
Glioblastoma is aggressive, highly infiltrating, and the most frequent malignant form of brain cancer. With a median survival time of only 14.6 months, when treated with the standard of care, it is essential to find new therapeutic options. A specific CDK4/6 inhibitor, PD0332991, obtained accelerated approval from the Food and Drug Administration for the treatment of patients with advanced estrogen receptor-positive and HER2-negative breast cancer. Common alterations in the cyclin D1-Cyclin Dependent Kinase 4/6-Retinoblastoma 1 pathway in glioblastoma make PD0332991 also an interesting drug for the treatment of glioblastoma. Promising results in in vitro studies, where patient derived glioblastoma cell lines showed sensitivity to PD0332991, gave motive to start in vivo studies. Outcomes of these studies have been contrasting in terms of PD0332991 efficacy within the brain: more research is necessary to conclude whether CDK4/6 inhibitor can be beneficial in the treatment of glioblastoma.